Effects of Steel Fibers Geometry on the Mechanical Properties of SIFCON Concrete - Shahad S. Khamees; Mohammed M. Kadhum; Nameer A. Alwash (Civil Engineering Journal, 2020)
This research aims to shed light on the effect of steel fiber shape, length, diameter, and aspect ratio on the mechanical properties of slurry infiltration fiber reinforced concrete (SIFCON). This study comprised of casting and testing three groups of SIFCON specimens with 6% fiber volume fraction. The first group was reinforced with micro steel fiber, other reinforced by hook end steel fibers, while the last group of specimens reinforced by mixing two shape of steel fiber as hybrid fiber (3% micro steel fiber +3% hook end steel fiber). Silica fume was used as a partial replacement (10%) by weight of cement. 3.7% super plasticizer was used to make the slurry liquid enough to penetrate through the fiber network, while the w/c ratio kept constant at 0.33. It was found from the results achieved that the compressive strength, static modulus of elasticity, splitting tensile strength and toughness are extremely affected by the geometry of fibers because the network of fibers formed and their density depends on the size and shape of fibers. Where the values of micro steel fibers are far outweighing the values of hooked end fibers. It was also deduced from empiricism results that combining long and short fibers gives excellent results.